THE USE OF ENGLISH IN INDONESIAN ADOLESCENT'S SLANG - I Dewa Putu Wjana Wijana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2012)
This paper aims at describing the use of English in Indonesian Adolescent's slang broadly known as bahasa gaul, the colloquial variation that symbolizes intimate relationships among the youngsters. By using data extracted from three slang dictionaries and applying distributional and identity method, the investigation finds that according to the form, the English slangy expressions can be classified into word (either mono morphemic or poly morphemic word), phrase, and sentence. The monomorphemic words are mainly created through various phonological change or orthographical alterations. Meanwhile, the poly morphemic words may be constructed through affixation, reduplication, internal modification, contraction and compounding processes. The vernacular phrases and sentences may consist of English words or mixture of lndonesian and English element. Finally, nearly all of slangy expressions experience semantic and translational deviations which ate intentionally created for fulfilling various communicative purposes.